Frequency and Seasonal Distribution of Plasmodium falciparum and Plasmodium vivax in Children in Tertiary hospital, Karachi - Pakistan - Mohammad Yaseen,; Hassan Ali, Nafisa (International Journal of Endorsing Health Science Research, 2015)
Background Malaria vector born disease caused by Plasmodium species is transmitted through female anopheles mosquito. It is becoming a serious health challenge in Pakistan listed among top ten malaria endemic countries. In year 2012, 85,000 malarial cases reported across Sind province. Accumulation of water and poor public healthcare system in post monsoon season facilitates breeding of vector resulting in an increase prevalence of malaria. This study aimed to observe the rate of malaria in children (mean age 07 years) with fever, high temperature, headache and shivering who visited Civil hospital in year 2013. Evaluation of month wise and seasonal distribution of malarial species found to cause disease in Karachi-Pakistan was done. Methods Blood samples collected through finger prick observed by thick and thin microscopy. Immuno chromatography performed to confirm negative microscopy results. Results During period of twelve month, 5519 blood samples screened and 947(18%) found positive for malaria parasites. Most frequent species P. vivax (76%) followed by P. falciparum (24%). Seasonal distribution of malaria patients were 105 in winter, 306 in pre monsoon and 519 in post monsoon. In months of March to September 97-100 % P. vivax species documented and in October to February both P. falciparum and P. vivax found in ratio 1:1. Conclusions Proper awareness regarding wearing of proper protective clothing should be imparted to low socioeconomic people. Non-government and civilian bodies should encourage local population to actively participate in clearing mosquito breeding sites. As number of malarial patients are increasing it is recommended that malaria control programme should also focus on research regarding development of novel compound/synergistic combination effective against drug resistant plasmodium species and anopheles mosquito.